Research on Silicon-based Planar Spiral Inductance Coil Based on Microelectromechanical System - Gang Li; Xiaofeng Zhao; Dianzhong Wen; Yang Yu (Universitas Ahmad Dahlan, 2015)
This paper describes a kind of silicon-based plane spiral inductance coil ,whose layout size and fabrication technology process are given. The production of inductance coil adopts the method of an internal down-lead produced by ohm contact electrode which is formed by heavily boron- diffused and the Al evaporated on the surface of N-type high resistivity silicon wafer. Processing the silicon cup on The back of the silicon wafer using Microelectromechanical system (MEMS) technology, on the basis of thickness reduction of the inductance coil substrate, the porous array substrate of about 5μm thickness is obtained by laser drilling on the underside of the silicon cup, which reduces the vortex of substrate, and greatly improves the Q value of inductance coil. Analyze the effects of series resistance of the coil and metal layer thickness on the Q value in the condition of low frequency and high frequency, and Ansys software is used to simulate the inductance coil current density and magnetic induction intensity, to determine the optimum substrate thickness of inductance coil. The silicon-based plane spiralind inductance coil has the advantages of simple manufacturing process and is compatible with IC technology, compared with other manufacturing method, so it has a wide application prospect.